CHARACTERISTICS OF STUDENTS' MATHEMATICAL PROBLEM SOLVING ABILITIES IN OPEN-ENDED-BASED VIRTUAL REALITY GAME LEARNING - Surya Amami Pramuditya; Muchamad Subali Noto; Fuji Azzumar (Jurnal Infinity, 2022)
This research is motivated by the problem-solving ability of students is still low, and the teaching materials used cannot be studied independently. The purpose of this study was to determine students' profiles about students' problem-solving abilities seen from indicators of choosing and implementing the problem-solving strategies to solve mathematical and outside mathematics using open-ended-based virtual reality games. A virtual reality game through open-ended-based learning media is made with the concept of moving the situation of learning mathematics in the real world into a virtual world displayed through a computer. This research used a qualitative method with a case study design. The research instrument used is a question of mathematical problem-solving ability through open-ended-based and interview transcripts. The research subjects were six eighth grade Junior High School students consisting of two students with high knowledge, two with moderate knowledge, and two with common knowledge. The result showed that students have different mathematical problem-solving abilities from each indicator, namely 1) identifying the adequacy of data for problem-solving, 2) making mathematical models from everyday situations or problems, 3) selecting and implementing strategies to solve math and math problems outside of using virtual reality games through open-ended based.